2022
DOI: 10.3390/ma15196783
|View full text |Cite
|
Sign up to set email alerts
|

Eddy Current Testing of Artificial Defects in 316L Stainless Steel Samples Made by Additive Manufacturing Technology

Abstract: Additive manufacturing has many positives, but its incorporation into functional parts production is restricted by the presence of defects. Eddy current testing provides solutions for their identification; however, some methodology and measurement standards for AM (additive manufacturing) products are still missing. The main purpose of the experiment described within this article was to check the ability of eddy current testing to identify AM stainless steel parts and to examine the data obtained by eddy curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…If we wanted to achieve a much worse classification scale, we would have to focus on the chemical composition (properties) of the degreaser, the temperature of the solution, the time of degreasing. [14], [17].…”
Section: Discussionmentioning
confidence: 99%
“…If we wanted to achieve a much worse classification scale, we would have to focus on the chemical composition (properties) of the degreaser, the temperature of the solution, the time of degreasing. [14], [17].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the method can detect surface and shallow defects in a conductive material. For a similar process, Gelatko et al [16] used eddy current sensors on the artificially generated defects in samples made up of 316L stainless steel. The study found that the testing method not only detected the defects but also helped in characterising the shape and size of defects.…”
Section: Imaging Defectsmentioning
confidence: 99%
“…The materials that form the matrices of the composites belong to the group of engineering (structural) or highly durable (high-tech) polymer composites. From the group of structural polymers, the PBT material (polybutylene terephthalate) and PPA material (polyphthalamide) were selected [ 13 , 14 ].…”
Section: Experiments Preparationmentioning
confidence: 99%